Pengaruh Brand Ambassador, Brand Image dan Brand Trust terhadap Keputusan Pembelian pada Produk Scarlett Whitening di Kota Denpasar - Utari, Ni Nyoman Anik; Yudy Wijaya, Putu; Alit Suputra, Gusti (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Purchasing decisions are important things to note because this will certainly consider how the company will then implement its marketing strategy. The purpose of this study is to determine the influence of brand ambassadors, brand image and brand trust on purchasing decisions. The location of this research was conducted in the city of Denpasar and the sample used was 150 respondents using a purposive sampling method. Data analysis techniques used are validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test and F test. From the results of the study it can be seen that brand ambassadors have a significant positive effect on purchasing decisions, brand image has a significant positive effect on purchasing decisions , brand trust has a significant positive effect on purchasing decisions, and brand ambassador, brand image and brand trust simultaneously have a positive and significant effect on purchasing decisions. The magnitude of the influence of the independent variables on purchasing decisions is 65.2 percent.